Electronic Payment Systems as a Driver of Digital Transformation in Islamic Banks: An Empirical Analysis Using the Islamic Technology Acceptance Model (ITAM) - Zoulikha, BEKHTI; Hayat, NABER (Journal of Ecohumanism, 2025)
This study examines the role of electronic payment systems in driving digital transformation in Islamic banks through the lens of an adapted Islamic Technology Acceptance Model (ITAM). Using balanced panel data from 8 Islamic banks over the period 2018–2023 (48 observations), the research applies Panel Fixed Effects, System GMM, and moderation analysis.The results reveal that electronic payment adoption has a strong positive and statistically significant impact on the Digital Transformation Index (β = 0.481, p < 0.01). Shariah governance quality positively moderates this relationship (β = 0.176, p < 0.01). The model explains 69.2% of the variance in digital transformation. These findings, derived from secondary data, provide empirical support for the applicability of ITAM in Islamic banking and highlight the enhancing role of strong Shariah governance in digital innovation.